2019
DOI: 10.33594/000000011
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondria-Targeted Metabolic Tubular Injury in Diabetic Kidney Disease

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 65 publications
3
39
0
Order By: Relevance
“…These findings are consistent with a recent observation that MetS patients with CKD (Jiang et al, 2019) have increased apoptosis and impaired ΔΨm in renal tubules but not podocytes (Jiang et al, 2019). Furthermore, oxidative stressmediated perturbance of glycolysis and tricarboxylic acid cycle contributes to the tubular injury in MetS (Jiang et al, 2019). The injury in human renal proximal tubule cells caused by highglucose in the medium is reversed by the mitochondria-targeted antioxidant, MitoQ (Xiao M. et al, 2017), that is related to the restoration of the Nrf2 expression, inhibition of the expression of Kelch-like ECH-associated protein (Keap1), and the interaction between Nrf2 and Keap1 (Xiao L et al, 2017).…”
Section: Renal Dysfunction In Metabolic Syndromesupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with a recent observation that MetS patients with CKD (Jiang et al, 2019) have increased apoptosis and impaired ΔΨm in renal tubules but not podocytes (Jiang et al, 2019). Furthermore, oxidative stressmediated perturbance of glycolysis and tricarboxylic acid cycle contributes to the tubular injury in MetS (Jiang et al, 2019). The injury in human renal proximal tubule cells caused by highglucose in the medium is reversed by the mitochondria-targeted antioxidant, MitoQ (Xiao M. et al, 2017), that is related to the restoration of the Nrf2 expression, inhibition of the expression of Kelch-like ECH-associated protein (Keap1), and the interaction between Nrf2 and Keap1 (Xiao L et al, 2017).…”
Section: Renal Dysfunction In Metabolic Syndromesupporting
confidence: 94%
“…Metabolomics analysis demonstrated that the suppression of mitochondrial metabolism and activity in patients with MetS is associated with lower gene expression of PGC1α (a master regulator of mitochondrial biogenesis) and less mitochondria DNA and protein content in the kidney ( Sharma et al, 2013 ). These findings are consistent with a recent observation that MetS patients with CKD ( Jiang et al, 2019 ) have increased apoptosis and impaired ΔΨm in renal tubules but not podocytes ( Jiang et al, 2019 ). Furthermore, oxidative stress-mediated perturbance of glycolysis and tricarboxylic acid cycle contributes to the tubular injury in MetS ( Jiang et al, 2019 ).…”
Section: Renal Dysfunction In Metabolic Syndromesupporting
confidence: 93%
“…In our previous study, we found acute hyperglycemia could lead to obvious renal oxidative stress activation and notable mitochondria damages including mitochondria swelling and irrecognizable mitochondrial crista (2). ROS is mainly produced by mitochondria, and excess ROS accumulation can aggravate mitochondria damages and even cell apoptosis (5). Clearing away damaged mitochondria in time is crucial for cellular homeostasis.…”
Section: Introductionmentioning
confidence: 98%
“…The accumulation of damaged mtDNA, fragmented mitochondria, activated apoptosis, loss of MMP, and perturbations in glycolysis and TCA cycle were detected in tubules and PBMCs from the patients. These results indicate that mitochondrial damage may be the hallmark of DKD patients (Jiang et al, 2019).…”
Section: Mitochondrial Haplogroups Associated With Disease In East Asiamentioning
confidence: 88%